Redesain Museum Kota Surabaya - Shylona Gratia Aurelius; Sherly de Yong; Hendy Mulyono (Intra, 2018)
This interior design project is a re-design of Surabaya City Museum with the concept of Surabaya’s Memory Lane. Most people in Surabaya are not aware with the existence of Surabaya Museum that is located in Siola due to lack of promotion and its plain appearance. Moreover, the museum in Surabaya is in a downturn due to lack of interest. Therefore the design of this Surabaya City Museum will revive the interest of Surabaya people and tourists to come and visit this Museum. In addition, this museum is also intended for education. The people of Surabaya should know the history of their own city and how hard was the struggle of the people in the past to make Surabaya as it is today. The design will use the concept of Surabaya’s Memory Lane which seems to invite visitors to get around the old town of Surabaya. Design will be made as attractive as possible by adjusting to the characteristics of Surabaya people who loves everything instant and beautiful. Explanation of each collection will be made as sophisticated and interesting as possible to make it easier for visitors to understand the history of the collection. The target of this museum is for all ages from the young to the old, inteded for the people of Indonesia and the tourists.